1969
DOI: 10.1136/gut.10.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Cell turnover in the rat small intestinal mucosa: an appraisal of cell loss.

Abstract: Part I Cell loss in rats with a normal mucosaThe concept of continuous epithelial renewal in the gastrointestinal tract was introduced at the end of the nineteenth century (Patzelt, 1882;Bizzozero, 1888;Schaffer, 1891), and since then labelling experiments with tritium-labelled thymidine have established that epithelial cells are produced in the crypts of the small intestinal mucosa, migrate up onto the villi and are lost at the tips, both in experimental animals (Leblond and Messier, 1958;Quastler and Sherman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1972
1972
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…These findings are similar to the observations that the upper small intestines of humans and of rats are relatively free of microorganisms [13,19].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings are similar to the observations that the upper small intestines of humans and of rats are relatively free of microorganisms [13,19].…”
Section: Discussionsupporting
confidence: 81%
“…This method requires relatively long periods of time and specialized knowl edge of histological techniques. In the past few years, Croft et al [5,6], Da Costa et al [7], Lof.hry et al [19], and G oldsmith [9], have introduced a new method for measuring rate of cell loss. In this procedure, the amount of deoxyribonucleic acid (DNA) collecting in a unit of time in the intestinal luminal fluids is equated with desquamation rate.…”
mentioning
confidence: 99%
“…Croft et al [9] have estimated that half a million cells each minute are lost from a segment of small intestine 5 cm long, and Loehry el al. [23] have shown that iron is lost into the gut by this route. As yet the only reliable method by which cell loss from the small intestine may be measured is by estimation of desoxyribonucleic acid in small intestinal washings [10].…”
Section: Discussionmentioning
confidence: 99%
“…(c) The epithelial cells must come only from the segment under study. In rat experiments this was ensured by tieing off either end of the small intestine and washing the whole small bowel of the living anaesthetised animal [33]. In man this has been done at the time of surgery [34] with results that com pare well with those obtained by the intestinal perfusion technique described above [18].…”
Section: Dna Loss As a Measure O F Cell Loss And Turnovermentioning
confidence: 70%